2015
DOI: 10.4081/aiua.2015.2.158
|View full text |Cite
|
Sign up to set email alerts
|

Use of transvaginal ultrasound in females with primary bladder neck obstruction. A preliminary study

Abstract: TVUS results worthy in the evaluation of patients with PBNO before and after surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The major utility of ultrasound scanning in women with BOO is in detecting possible complications such as bladder wall thickening or upper tract dilatation/hydronephrosis. One study reported that transvaginal ultrasonography was able to demonstrate a closed bladder neck during attempts at micturition and concluded that this modality was useful for the evaluation of possible causal factors in female BOO [38].…”
Section: 213mentioning
confidence: 99%
“…The major utility of ultrasound scanning in women with BOO is in detecting possible complications such as bladder wall thickening or upper tract dilatation/hydronephrosis. One study reported that transvaginal ultrasonography was able to demonstrate a closed bladder neck during attempts at micturition and concluded that this modality was useful for the evaluation of possible causal factors in female BOO [38].…”
Section: 213mentioning
confidence: 99%
“…The characteristics of the 28 included studies are detailed in Table 1 and Supplementary Table 2. Of these, 25 evaluated the use of UDS AE fluoroscopy [4,[10][11][12][13][14][15][16][17][18][19][20][21][22][26][27][28][29][30][31][32][33][34][35][36], two of which evaluated pre-existing nomograms [35,36], one evaluated the use of transvaginal ultrasound scan (TVUS) and voiding UDS [23], and two looked at transperineal Doppler ultrasound scan (TPUS) [24,25]. Five studies defined cut-offs for UDS parameters [17,26,29,31,32], one study described fluoroscopic characteristics for fBOO [20], one study evaluated the area under the curve (AUC) of detrusor pressure [18], and three studies derived a nomogram to diagnose fBOO [10,14,19].…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…Galica et al [23] investigated the role of TVUS in women with LUTS suggestive of BOO, and Q max <12 ml/s and P det.…”
Section: Transvaginal Ultrasound Scanmentioning
confidence: 99%
“…In patients with suspected PBNO on video-urodynamics, transvaginal ultrasound (TVUS) was performed at rest (basal) and during voiding (25). TVUS findings in these patients were characterized by a closed bladder neck during both rest and voiding.…”
Section: Imagingmentioning
confidence: 99%